The Evolution of Stem as a Concept, in Science Education – A 21st Century Perspective - Costa, King; Ntsobi, Mfanelo, Patrick; Siwahla-Madiba, Nandipha, Daphne (My University, 2023)
The transition from STEM to STEAM education signifies a profound shift in contemporary pedagogy, acknowledging the need to integrate not just science, technology, engineering, and mathematics but also the arts into the learning process. This transformation is primarily driven by evolving job market demands, necessitating a more comprehensive skill set in students. Practical implications of this shift involve creative teaching techniques and technologies that foster imagination, experiential learning, and interdisciplinary comprehension. However, within the STEAM domain, significant knowledge gaps remain, offering opportunities for further exploration and development. The primary knowledge gap involves framing STEAM from an enactive-ecological viewpoint. While broader STEM and STEAM research is well-established, the application of enactive and ecological theories in the context of STEAM education is largely uncharted territory. Addressing this gap has the potential to enhance STEAM pedagogy by integrating insights from these theories into educational practices. The second gap relates to the technical underpinnings of integrated teaching and learning in STEM/STEAM contexts. Seamless integration of knowledge domains is vital for meaningful learning experiences that transcend traditional disciplinary boundaries. Robust technical foundations are needed, encompassing digital learning ecosystems, interdisciplinary content development, innovative pedagogical frameworks, accessibility, and inclusivity, professional development for educators, data analytics, and assessment, collaborative environments, real-world application, and immersive technologies. The third gap involves the incorporation of mixed reality (XR) as an educational technology approach within the STEAM framework from an enactive-ecological perspective. XR technologies, including augmented reality (AR), virtual reality (VR), and mixed reality, have the potential to greatly enhance STEAM education. However, further research is required to maximize the use of these technologies from an enactive-ecological standpoint, emphasizing active learning, sensorimotor engagement, experiential learning, and contextual understanding. The fourth knowledge gap emphasizes the importance of ongoing research in the STREAM (STEM + Research + Arts) narrative. Research is a cornerstone for advancing our understanding of the efficacy of various pedagogical approaches, the impact of integrating arts into STEM, the role of enactive-ecological theories, the outcomes of immersive technologies, and the development of unified models for interdisciplinary learning. Strong research practices inform evidence-based teaching and consistently enhance STEAM education. Finally, transition from STEM to STREAM is a crucial development in education, equipping students with the skills and knowledge needed to thrive in a rapidly changing world. While this shift promotes innovative teaching methods and technologies, addressing the identified knowledge gaps and prioritizing research are essential to fully realize the potential of STEAM education. Ultimately, it empowers students to excel in a dynamic and complex global landscape while advancing educational practices through empirical research and evidence-based approaches.
Keywords: Educational Science; Research education; STEAM Education; STEM Education; STREAM Education